Directed Nickel‐Catalyzed pseudo‐Anomeric C−H Alkynylation of Glycals as an Approach towards C‐Glycoconjugate Synthesis. Issue 22 (20th September 2021) - de Robichon, Morgane; Branquet, David; Uziel, Jacques; Lubin‐Germain, Nadège; Ferry, Angélique
Abstract: The synthesis of complex C ‐glycoconjugates is presented here using a key directed nickel‐catalyzed C−H alkynylation step. Thanks to a bidentate amidoquinoline‐type directing group, the insertion of diverse alkynyl moieties onto the pseudo ‐anomeric position of glycal substrates was performed on ten examples in moderate to good yields. These platforms were used as starting substrates in a click reaction with complex azides to form original C ‐glycoconjugates. By this route, a C ‐glycosylated amino acid, a C ‐linked disaccharide and a C ‐glycosylated biotin derivative were synthesized. Preliminary conditions to remove the directing group are also proposed. Abstract :